Scientific and ethical follow-up of the development of a creative personality - Ryndak, Valentina G.; Sal’dayeva, Ol’ga V. (Opción, 2019)
The article makes the importance of critical and creative attitude towards the world and censoriousness of a person important and actual. The poll results, interrogations, tasks performed, analysis of the modern creative education system, students’ activity observations, content analysis and author’s experience with qualitative-quantitative method served as a source of material for the research. As a result, the country which cannot achieve high scientific progress tempo and its usage in all the spheres of life will be considered an outsider. Students gradually come to a conclusion that creativity can be developed, and scientific and ethical follow-up is important for them.